The influence of korean celebrities as brand ambassador and product quality on purchase decision with brand image as the mediating variable on Scarlett Whitening - Novelia, Novelia; Azazi, Anwar; Purmono, Bintoro Bagus; Rosnani, Titik; Hendri, M. Irfan (Enrichment : Journal of Management, 2023)
Every corporation employs diverse marketing strategies with the anticipation of significantly impacting the company's advancement. One such strategy involves the engagement of a brand ambassador entrusted by the company to cultivate a brand image for the company. The brand image is deemed influential in persuading consumers to place trust in the company, thereby compelling them to make product purchases. The primary objective of this research is to examine the influence of Korean Celebrities as Brand Ambassadors and Product Quality on Purchase Decisions. In this context, Brand Image assumes the role of a mediating variable for Scarlett Whitening. The study adopts a quantitative approach utilizing purposive sampling techniques. It employs Structural Equation Modeling (SEM) with the assistance of AMOS 24 statistical software to analyze and assess the measurement and structural models of the research construct.